(untitled) (Andamios, Revista de Investigación Social, 2015)
In this paper, I approach one of the first discursive constructions of the history of the New Spain, the poem Nuevo mundo y conquista, written by Francisco de Terrazas, a creole, in the late sixteenth century. For this, I outline the creation of a creole class, heir to the feeling of nobility of the first conquerors of America, and then I analyze the writing of Nuevo mundo y conquista in the context of these considerations.